PENENTUAN DISTRIBUSI INDUKSI MAGNETIK YANG DITIMBULKAN OLEH BERBAGAI JENIS TELEPON SELULER DENGAN MENGGUNAKAN PROBE MAGNETIK PASCO - Herianto '; Erwin '; Mbantun Ginting (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The distribution of induced magnetic field due to various kinds of cellular telephone has been investigated. The induced  magnetic  field was measured using  Magnetic  Probe Pasco in two directions  namely  horizontal  dan  vertical. In horizontal direction the induced  magnetic  field  was  measured  with the distance of 0,5 cm above the cellular telephone.  The result showed that the  widest  distribution of  magnetic  field  was generated by Sony Ericcson cellular telephone, while Samsung cellular  telephone generated the narrowest value of induced  magnetic  field.  Moreover,  the highest and lowest  value    induced  magnetic  field  were  generated  by Sony Ericcson and Sony were 2,4x10-3Tesla and 1,2x10-3Tesla respectively. In  vertical  direction,  the induced magnetic  field was reduced significantly  the  as measured  away from the cellular telephone. The value of magnetization  was  highest from Samsung cellular telephone and  the  lowest from Blackberry. The value of magnetization from Samsung and Blackberry was 9,26x10-5emu/cm3 and 7,16x10-5emu/cm3 , respectively.